Downregulation of HuR as a new mechanism of doxorubicin resistance in breast cancer cells - Latorre, Elisa (BioMed Central, 2012)
BACKGROUND: HuR, an RNA binding protein involved in the post-transcriptional regulation of a wide spectrum of mRNAs, has been demonstrated to be a determinant of carcinogenesis and tumor aggressiveness in several cancer types. In this study, we investigated the role of HuR in the apoptosis and in the chemoresistance induced by the widely used anticancer drug doxorubicin in human breast cancer cells (MCF-7). RESULTS: We showed that HuR acts in the early phase of cell response to doxorubicin, being induced to translocate into the cytoplasm upon phosphorylation. Reducing HuR levels diminished the apoptotic response to doxorubicin. Doxorubicin-induced apoptosis was also correlated with the presence of HuR in the cytoplasm. Rottlerin, which was able to block HuR nuclear export, had correspondingly antagonistic effects with doxorubicin on cell toxicity. The proapoptotic activity of HuR was not due to cleavage to an active form, as was previously reported. In in vitro selected doxorubicin resistant MCF-7 cells (MCF-7/doxoR) overexpressing the multidrug resistance (MDR) related ABCG2 transporter, we observed a significant HuR downregulation that was paralleled by a corresponding downregulation of HuR targets and by loss of rottlerin toxicity. Restoration of HuR expression in these cells resensitized MCF-7/doxoR cells to doxorubicin, reactivating the apoptotic response. CONCLUSIONS: The present study shows that HuR is necessary to elicit the apoptotic cell response to doxorubicin and that restoration of HuR expression in resistant cells resensitizes them to the action of this drug, thereby identifying HuR as a key protein in doxorubicin pharmacology.